2021
DOI: 10.1111/aos.14997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of topical insulin with autologous serum eye drops in persistent epithelial defects of the cornea

Abstract: Purpose To investigate the effect of topical insulin on epithelization in persistent epithelial defects (PED) refractory to usual treatment compared to autologous serum. Design Retrospective, consecutive case–control series. Methods The charts of 61 consecutive patients with PED treated with topical insulin (case group) and 23 treated with autologous serum (control group) were reviewed. Primary efficacy end points were the percentage of patients in which epithelization was achieved, as well as the rate and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Moreover, NGF drops has been suggested by them 1 and others authors. 17 Along the same lines, Diaz-Valle et al 18 proposed topical insulin as an effective and safe treatment for the management of PED. This treatment presented also better epithelization outcomes than AS, so they suggest that it could be first-line treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, NGF drops has been suggested by them 1 and others authors. 17 Along the same lines, Diaz-Valle et al 18 proposed topical insulin as an effective and safe treatment for the management of PED. This treatment presented also better epithelization outcomes than AS, so they suggest that it could be first-line treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Cruz‐Cazarim et al 13 showed that INS could treat dry eye syndrome and corneal injuries. Morever, a recent clinical study suggested that topical INS was an effective way to safely promote the healing of persistent epithelial defects in patients who were unresponsive to standard treatment 14 . However, the use of INS in the treatment of corneal alkali burns has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Morever, a recent clinical study suggested that topical INS was an effective way to safely promote the healing of persistent epithelial defects in patients who were unresponsive to standard treatment. 14 However, the use of INS in the treatment of corneal alkali burns has been rarely reported. We hypothesize that the local application of INS may be a promising strategy for the treatment of corneal alkali burns due to its antioxidant capacity.…”
mentioning
confidence: 99%
“…They are known to usually be resistant to healing with standard therapy such as frequent preservative-free artificial tears, ointments or gels, press patching, punctal plugging, and therapeutic contact lens wear. Several favorable results have been reported in PEDs associated with the use of autologous serum eye drops, insulin eye drops, amniotic membrane extract eye drops, epidermal growth factor (EGF) ointment, and recently developed topical recombinant human nerve growth factor (Cenegermin) [1][2][3][4][5][6][7]. However, PEDs that do not respond to even these drops need more aggressive methods to restore ocular surface health.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous serum eye drops were introduced decades ago and known to contain several substances that aid in the regeneration of the keratoconjunctival epithelium, and many reports show their positive effects on neurotrophic PEDs [1][2][3][4]. Ointments or gels-though accompanied by concomitant visual blurring-are preferred modalities as conservative treatments for exposure keratopathy in lagophthalmos because of the increased contact time with the cornea [12].…”
Section: Introductionmentioning
confidence: 99%